Exploring new interregional opportunities for pharmaceutical supply chains: The potential of Mercosur countries to advance the EU's Global Health Strategy - Fernanda Cimini Salles; Michael Bayerlein; Pedro A. Villarreal; Franziska Schwebel (Stiftung Wissenschaft und Politik (SWP), 2024)
The European Union's (EU) Global Health Strategy calls for open and strategic autonomy in the field of pharmaceuticals, which would lead to the redesign of EU global supply and value chains as well as trade relations. As the EU and Germany are seeking to diversify their trade partners, the Mercosur countries offer latent potential. Mercosur is the name of the South American trade bloc consisting of Argentina, Brazil, Paraguay and Uruguay, with Venezuela's membership currently suspended. The associate states of the bloc are Chile, Peru, Colombia, Ecuador, Guyana and Suriname. Bolivia is currently awaiting final approval to become a full member of the bloc.
Keywords: 320; pharmaceutical supply chains; Mercosur countries; EU's Global Health Strategy; Argentina; Brazil; Paraguay; Uruguay; Chile; Peru; Colombia; Ecuador; Guyana; Suriname; Bolivia; free trade agreement (FTA); European Medicines Agency (EMA); Health Emergency Preparedness and Response Authority (HERA)